Nonlinear Effects in Rolling Mills Dynamics - Krot, Pavel V.; Korennoy, Vladimir V. (NTU "KhPI", 2016)
This paper intends to describe nonlinear effects occurring in rolling mills dynamics. That is necessarily for vibrations damping and reliable diagnostics of rolling mills equipment under non-stationary working conditions. Three types of nonlinear effects are investigated taking place in drivelines and stands of different design, namely, transient torsional vibrations in hot rolling mills, chatter vibrations in tandem cold rolling mills and parametrical vibrations in high-speed wire and rod rolling mills. The procedure is proposed for natural frequencies identification when short transient torque signals restrict application of the Fourier transform. Some considerations given on using nonlinear effects for wear diagnostics and vibrations control based on natural frequencies and modes analysis of multi-body systems.
Keywords: rolling mills; nonlinear vibrations; chatter identification